Antibacterial stainless steel band with high surface quality and preparation method thereof

Through the treatment of silver nano particles and chitosan puppets on the stainless steel band, combined with the mixed solution of dopamine-eighteen amine, forming a dual antibacterial mechanism, solving the single and surface quality of the existing antibacterial stainless steel band antibacterial mechanism Insufficient problems achieved efficient and stable antibacterial properties.

CN119332318AActive Publication Date: 2025-01-21JIANGSU YONGJIN METAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411885709.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-01-21
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The antibacterial mechanism of the existing antibacterial stainless steel strip is single, easily affected by environmental factors, and insufficient surface quality, resulting in unstable antibacterial performance.

Method used

By depositing silver nanoparticles and coupling heterojunctions with chitosan on stainless steel strips, combined with a mixed solution of dopamine-octadecylamine, a dual antibacterial mechanism is formed, and the surface quality is improved through specific process steps.

Benefits of technology

A variety of antibacterial mechanisms are realized, the stability and service life of antibacterial properties are improved, and the expansion of market demand and application scenarios is met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an antibacterial stainless steel band with high surface quality and a preparation method thereof, and relates to the technical field of antibacterial stainless steel bands, and the preparation method comprises the following steps: smelting an iron alloy raw material, introducing argon into a steel ladle after tapping, stirring molten steel, uniformly mixing, and continuously casting the molten steel into a blank; the casting blank is sequentially subjected to cogging, hot rolling, cold rolling, annealing, solid solution treatment and aging treatment, and a stainless steel band base material is obtained; the method comprises the following steps: by taking a stainless steel band as a working electrode, a platinum plate as a counter electrode and a saturated calomel electrode as a reference electrode, carrying out silver nanoparticle deposition in an aqueous electrolyte through a three-electrode deposition system, taking out and drying to obtain an electro-deposition modified stainless steel band; and the electrodeposition modified stainless steel band is soaked in a dopamine-octadecylamine mixed solution, heating reaction is conducted, ultrasonic washing is conducted through ethyl alcohol, room-temperature drying is conducted, then the electrodeposition modified stainless steel band is soaked in a chitosan coupling heterojunction solution, room-temperature maintaining, deionized water washing and vacuum drying are conducted, and the antibacterial stainless steel band is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of antibacterial stainless steel belts, in particular to an antibacterial stainless steel belt with high surface quality and a preparation method thereof. Background Art

[0002] With the advancement of science and technology and the improvement of people's living standards, antibacterial materials are increasingly used in the fields of medical treatment, food processing, construction, etc. Among them, antibacterial stainless steel strips have attracted much attention due to their excellent mechanical properties and corrosion resistance. However, the existing antibacterial stainless steel strips still have some significant defects in practical applications.

[0003] First, the antibacterial mechanism of many antibacterial stainless steel strips is relatively simple, mainly relying on the addition of antibacterial agents or the release of metal ions such as silver and copper on the surface. Although these antibacterial agents are effective, they may be affected by environmental factors such as temperature and humidity in actual applications, resulting in reduced antibacterial effects. In addition, some antibacterial agents may migrate or precipitate during use, which may cause potential harm to the environment or human health.

[0004] Secondly, the existing antibacterial stainless steel belts also have deficiencies in surface quality. Traditional preparation methods often make it difficult to achieve high uniformity and delicate surface treatment, resulting in unstable antibacterial properties. In addition, materials with higher surface roughness are more favorable for bacterial attachment and growth, further reducing their antibacterial efficiency.

[0005] Therefore, there is an urgent need to develop a new type of antibacterial stainless steel belt, which not only has a diversified antibacterial mechanism, but also can improve its antibacterial performance while maintaining high surface quality to meet the growing market demand and application scenarios. Summary of the invention

[0006] The object of the present invention is to provide an antibacterial stainless steel belt with high surface quality and a preparation method thereof, so as to solve the problems raised in the prior art.

[0007] To achieve the above object, the present invention provides the following technical solutions: A method for preparing an antibacterial stainless steel strip with high surface quality comprises the following steps: S1: smelting a ferroalloy raw material, introducing argon into a ladle after tapping to stir the molten steel and mix it evenly, and continuously casting the molten steel into a billet; S2: subjecting the ingot to blanking, hot rolling, cold rolling, annealing, solution treatment and aging treatment in sequence to obtain a stainless steel strip substrate; S3: Using a stainless steel strip as a working electrode, a platinum plate as a counter electrode, and a saturated calomel electrode as a reference electrode, silver nanoparticles are deposited in an aqueous electrolyte through a three-electrode deposition system, and then taken out and dried at 40-60°C for 4-6h to obtain an electrodeposited modified stainless steel strip; S4: The electro-deposited modified stainless steel strip is immersed in a mixed solution of dopamine-octadecylamine, heated to 37-38°C for reaction for 6-7h, ultrasonically washed with ethanol, dried at room temperature, immersed in 4-5mg / mL chitosan coupled heterojunction solution, kept at room temperature for 2-3h, washed with deionized water, and vacuum dried at 40-45°C for 8-12h to obtain an antibacterial stainless steel strip.

[0008] Further, the ferroalloy raw material includes any one or more of scrap steel, sponge iron, ferrochrome, ferromanganese, and ferrosilicon; Furthermore, the elemental composition of the stainless steel strip substrate includes, by mass percentage, C: 0.05-0.06, Mn: 4.4-4.6, Cr: 14.5-15, Ni: 5.5-6, Cu: 1.0-1.2, Ag: 0.6-0.8, Si: 1.2-1.4, S≤0.025, P≤0.060, Ce: 0.5-0.6, Ti: 0.4-0.6, and the rest are Fe and unavoidable impurity elements.

[0009] Furthermore, in step S2, the specific steps of forming the blank include casting, the casting temperature is 1150-1160°C; the hot rolling temperature is 1160°C-1180°C; the annealing temperature is 950-960°C; the solution temperature is 1200-1210°C, the solution time is 2-2.5h, the aging temperature is 620-630°C, and the aging time is 8-8.5h.

[0010] Furthermore, in the preparation process of the electrodeposited modified stainless steel strip, the aqueous electrolyte consists of 1 mM silver nitrate solution, 3-5 mM citric acid solution and 0.1 mM potassium nitrate solution; the silver nanoparticle deposition process includes a nucleation process and a growth process, the nucleation process parameters are: the nucleation potential is -0.7-0.8 V, the time is 100 s, and the growth process parameters are: the growth potential is -0.1 V, and the time is 600-3600 s.

[0011] Furthermore, in step S4, the mixed solution of dopamine-octadecylamine is composed of 2-3 mg / L dopamine hydrochloride Tris buffer solution and 50 mM octadecylamine ethanol solution.

[0012] Furthermore, the preparation method of the chitosan coupled heterojunction comprises the following steps: adding chitosan to 0.5-1% v / v acetic acid, heating to 50-52° C. and stirring for 1-1.5 h, cooling to room temperature, adding chitosan nanoparticles, stirring evenly, and obtaining a mixture A; adding N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and N-hydroxysulfosuccinimide to ethanol, stirring evenly, and obtaining a mixture B; adding a bismuth-based metal organic framework to a mixed solvent of deionized water and glycerol, stirring evenly, and obtaining a mixture C; adding the mixture B to the mixture A, stirring for 10-15 min, adding the mixture C, stirring at room temperature for 24 h, centrifuging, collecting the solid product, and washing with ethanol and deionized water to obtain a chitosan coupled heterojunction.

[0013] Furthermore, in the preparation process of the chitosan coupled heterojunction, the mass ratio of chitosan: chitosan nanoparticles: N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride: N-hydroxysulfosuccinimide: bismuth-based metal organic framework is 10:10-20:1:1:1.

[0014] Furthermore, the solvent of the chitosan coupling heterojunction solution is 0.5% v / v acetic acid.

[0015] Furthermore, the preparation method of the chitosan nanoparticles comprises the following steps: adding hematoporphyrin dihydrochloride and triethylamine to dimethyl sulfoxide, stirring at room temperature in the dark for 1-1.5 hours, adding 1,3-dicyclohexylcarbodiimide and N-hydroxysuccinimide, stirring at this temperature for 12-14 hours, filtering, collecting the filtrate, adding excess anhydrous ether, separating the precipitate, washing with methanol, and obtaining hematoporphyrin ester; adding chitosan to deionized water, stirring evenly, adding a dimethyl sulfoxide solution of hematoporphyrin ester under ice bath conditions, adding tetrabutylammonium bromide and 4-(N,N-dimethylamino)pyridine, stirring at room temperature in the dark for 72 hours, dialyzing with deionized water for 3 days, and freeze-drying to obtain a crude conjugate; adding the crude conjugate to a phosphate buffer, ultrasonically treating for 10-15 minutes, filtering with a 0.4-0.45 μm filter membrane, and obtaining chitosan nanoparticles.

[0016] Furthermore, in the preparation process of the hematoporphyrin ester, the mass ratio of hematoporphyrin dihydrochloride: triethylamine: 1,3-dicyclohexylcarbodiimide: N-hydroxysuccinimide is 10:10:6.2:3.5; in the preparation process of the crude conjugate, the mass ratio of chitosan: hematoporphyrin ester: tetrabutylammonium bromide: 4-(N,N dimethylamino)pyridine is 100:(8-12):0.5:0.5.

[0017] Furthermore, the preparation method of the bismuth-based metal-organic framework comprises the following steps: adding bismuth nitrate pentahydrate and trimesic acid to methanol, stirring the solution until it is clear, heating it to 120-125°C to react for 24 hours, centrifuging, collecting the solid product, washing it with methanol, and vacuum drying it at 70-75°C for 12 hours to obtain a bismuth-based metal-organic framework; during the preparation of the bismuth-based metal-organic framework, the mass ratio of bismuth nitrate pentahydrate: trimesic acid is 0.84056:0.2424.

[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention adds a complexing agent sodium citrate and adjusts the concentration of sodium citrate so that the complex formed by silver ions and citric acid can accelerate the electrodeposition speed, improve the current efficiency, and reduce the activation overpotential, thereby improving the electrodeposition process of silver nanoparticles; the complexing agent sodium citrate is added to the electrolyte so that (CitAg) 2− In Cit 3− With Ag + The complexation process between Ag + The reduction process of Ag + To Ag 0 The addition of excessive CitNa makes the silver ions mainly in the form of Ag m (Cit 3− ) n exists in the form of Ag + The ion part is Cit 3− Ion coating, thus promoting the regular deposition of Ag nanoparticles on the positive electrode. Ag nanoparticles are used to release Ag from the surface coating. + ions into the surrounding water medium, thereby promoting the production of reactive oxygen or directly destroying the cell membrane. At the same time, nano-Ag particles can be directly adsorbed on the cell membrane of bacteria, affecting membrane permeability and normal respiration. The coating formed by dopamine-octadecylamine on the surface of silver nanoparticles has a synergistic effect with the silver nanoparticles. On the one hand, the presence of silver nanoparticles helps to induce the adsorption of dopamine-octadecylamine complex on the surface; on the other hand, the presence of dopamine-octadecylamine coating helps to effectively control Ag. + The release of bacteria greatly increases the service life of the antibacterial stainless steel belt.

[0019] 2. The present invention couples hematoporphyrin to chitosan after activation, and prepares antibacterial chitosan nanoparticles based on photodynamic action through ultrasonic treatment and filtration. On this basis, a chitosan coupled heterojunction based on the coupling of chitosan and bismuth-based metal organic framework is synthesized. On the one hand, the active oxygen generated by hematoporphyrin under light can change the structure of nanoparticles by oxidizing the chitosan skeleton, thereby significantly improving the photodynamic antibacterial activity of hematoporphyrin; on the other hand, the chitosan coupled heterojunction has a higher electron-hole separation efficiency, improves the light absorption rate, especially visible light, prolongs the electron-hole life, reduces the band gap, and more electrons can be excited to enter the conduction band and participate in the photocatalytic reaction, thereby greatly improving the photocatalytic performance. The chitosan coupled heterojunction exhibits better photocatalytic antibacterial activity against Escherichia coli and Staphylococcus aureus than pure catalysts under visible light irradiation. Silver nanoparticles and chitosan coupled heterojunctions provide a dual antibacterial mechanism for antibacterial stainless steel belts, greatly expanding the application scenarios of antibacterial stainless steel belts and improving the service life of antibacterial stainless steel belts. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] In the following embodiment, the preparation method of chitosan nanoparticles comprises the following steps: adding 10 mg of hematoporphyrin dihydrochloride and 10 mg of triethylamine to 20 mL of dimethyl sulfoxide, stirring at room temperature in the dark for 1 h, adding 6.2 mg of 1,3-dicyclohexylcarbodiimide and 3.5 mg of N-hydroxysuccinimide, stirring at this temperature for 12 h, filtering, collecting the filtrate, adding excess anhydrous ether, separating the precipitate, washing with methanol, and obtaining hematoporphyrin ester; adding 100 mg of chitosan to deionized water, stirring evenly, adding a dimethyl sulfoxide solution containing 8 mg of hematoporphyrin ester under ice bath conditions, adding 0.5 mg of tetrabutylammonium bromide and 0.5 mg of 4-(N,N-dimethylamino)pyridine, stirring at room temperature in the dark for 72 h, dialyzing with deionized water for 3 d, and freeze-drying to obtain a crude conjugate; adding the crude conjugate to phosphate buffer, ultrasonically treating for 10 min, filtering with a 0.45 μm filter membrane, and obtaining chitosan nanoparticles.

[0022] In the following embodiment, the preparation method of the bismuth-based metal organic framework comprises the following steps: adding 0.84056 g of bismuth nitrate pentahydrate and 0.2424 g of trimesic acid to 40 mL of methanol, stirring the solution until it becomes clear, heating to 120° C. to react for 24 h, centrifuging, collecting the solid product, washing with methanol, and vacuum drying at 70° C. for 12 h to obtain a bismuth-based metal organic framework.

[0023] Embodiment 1: A method for preparing an antibacterial stainless steel strip with high surface quality, comprising the following steps: S1: smelting a ferroalloy raw material, introducing argon into a ladle after tapping to stir the molten steel and mix it evenly, and continuously casting the molten steel into a billet; S2: subjecting the ingot to blanking, hot rolling, cold rolling, annealing, solution treatment and aging treatment in sequence to obtain a stainless steel strip substrate; S3: Using a stainless steel strip as a working electrode, a platinum plate as a counter electrode, and a saturated calomel electrode as a reference electrode, silver nanoparticles are deposited in an aqueous electrolyte through a three-electrode deposition system, taken out, and dried at 40-60°C for 4-6h to obtain an electrodeposited modified stainless steel strip; wherein, in the step S2, the specific steps of blanking include casting blanking, the blanking temperature is 1150°C; the hot rolling temperature is 1160°C; the annealing temperature is 950°C; the solution temperature is 1200°C, the solution time is 2h, the aging temperature is 620°C, and the aging time is 8h; the aqueous electrolyte is composed of 1mM silver nitrate solution, 3mM citric acid solution and 0.1mM potassium nitrate solution; the silver nanoparticle deposition process includes a nucleation process and a growth process, the nucleation process parameters are: the nucleation potential is -0.7V, the time is 100s, and the growth process parameters are: the growth potential is -0.1V, and the time is 3600s; S4: Add 1g chitosan to 100mL 0.8% v / v acetic acid, heat to 50°C and stir for 1-1.5h, cool to room temperature, add 1g chitosan nanoparticles, stir evenly to obtain mixture A; add 0.1g N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 0.1g N-hydroxysulfosuccinimide to ethanol and stir evenly to obtain mixture B; add 0.1g bismuth-based metal organic framework to a mixed solvent of 20mL deionized water and 10mL glycerol and stir evenly to obtain mixture C; add mixture B to mixture A and stir for 10min, add mixture C, stir at room temperature for 24h, centrifuge, collect solid products, wash with ethanol and deionized water to obtain chitosan coupled heterojunction; S5: The electro-deposited modified stainless steel strip was immersed in a mixed solution of dopamine-octadecylamine, heated to 37°C for reaction for 6 hours, ultrasonically washed with ethanol, dried at room temperature, immersed in a 4 mg / mL chitosan coupled heterojunction solution, kept at room temperature for 2 hours, washed with deionized water, and vacuum dried at 40°C for 8 hours to obtain an antibacterial stainless steel strip.

[0024] Embodiment 2: A method for preparing an antibacterial stainless steel strip with high surface quality, comprising the following steps: S1: smelting a ferroalloy raw material, introducing argon into a ladle after tapping to stir the molten steel and mix it evenly, and continuously casting the molten steel into a billet; S2: subjecting the ingot to blanking, hot rolling, cold rolling, annealing, solution treatment and aging treatment in sequence to obtain a stainless steel strip substrate; S3: Using a stainless steel strip as a working electrode, a platinum plate as a counter electrode, and a saturated calomel electrode as a reference electrode, silver nanoparticles are deposited in an aqueous electrolyte through a three-electrode deposition system, taken out, and dried at 40-60°C for 4-6h to obtain an electrodeposited modified stainless steel strip; wherein, in the step S2, the specific steps of blanking include casting blanking, the blanking temperature is 1150°C; the hot rolling temperature is 1160°C; the annealing temperature is 950°C; the solution temperature is 1200°C, the solution time is 2h, the aging temperature is 620°C, and the aging time is 8h; the aqueous electrolyte is composed of 1mM silver nitrate solution, 3mM citric acid solution and 0.1mM potassium nitrate solution; the silver nanoparticle deposition process includes a nucleation process and a growth process, the nucleation process parameters are: the nucleation potential is -0.7V, the time is 100s, and the growth process parameters are: the growth potential is -0.1V, and the time is 3600s; S4: Add 1g chitosan to 100mL 0.8% v / v acetic acid, heat to 50°C and stir for 1-1.5h, cool to room temperature, add 2g chitosan nanoparticles, stir evenly to obtain mixture A; add 0.1g N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 0.1g N-hydroxysulfosuccinimide to ethanol and stir evenly to obtain mixture B; add 0.1g bismuth-based metal organic framework to a mixed solvent of 20mL deionized water and 10mL glycerol and stir evenly to obtain mixture C; add mixture B to mixture A and stir for 10min, add mixture C, stir at room temperature for 24h, centrifuge, collect solid products, wash with ethanol and deionized water to obtain chitosan coupled heterojunction; S5: The electro-deposited modified stainless steel strip was immersed in a mixed solution of dopamine-octadecylamine, heated to 37°C for reaction for 6 hours, ultrasonically washed with ethanol, dried at room temperature, immersed in a 4 mg / mL chitosan coupled heterojunction solution, kept at room temperature for 2 hours, washed with deionized water, and vacuum dried at 40°C for 8 hours to obtain an antibacterial stainless steel strip.

[0025] Embodiment 3: A method for preparing an antibacterial stainless steel strip with high surface quality, comprising the following steps: S1: smelting a ferroalloy raw material, introducing argon into a ladle after steel is tapped to stir the molten steel and mix it evenly, and continuously casting the molten steel into a billet; S2: subjecting the ingot to blanking, hot rolling, cold rolling, annealing, solution treatment and aging treatment in sequence to obtain a stainless steel strip substrate; S3: Using a stainless steel strip as a working electrode, a platinum plate as a counter electrode, and a saturated calomel electrode as a reference electrode, silver nanoparticles are deposited in an aqueous electrolyte through a three-electrode deposition system, taken out, and dried at 40-60°C for 4-6h to obtain an electrodeposited modified stainless steel strip; wherein, in the step S2, the specific steps of blanking include casting blanking, the blanking temperature is 1150°C; the hot rolling temperature is 1160°C; the annealing temperature is 950°C; the solution temperature is 1200°C, the solution time is 2h, the aging temperature is 620°C, and the aging time is 8h; the aqueous electrolyte is composed of 1mM silver nitrate solution, 3mM citric acid solution and 0.1mM potassium nitrate solution; the silver nanoparticle deposition process includes a nucleation process and a growth process, the nucleation process parameters are: the nucleation potential is -0.7V, the time is 100s, and the growth process parameters are: the growth potential is -0.1V, and the time is 3600s; S4: Add 1g chitosan to 100mL 0.8% v / v acetic acid, heat to 50°C and stir for 1-1.5h, cool to room temperature, add 2g chitosan nanoparticles, stir evenly to obtain mixture A; add 0.1g N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 0.1g N-hydroxysulfosuccinimide to ethanol and stir evenly to obtain mixture B; add 0.1g bismuth-based metal organic framework to a mixed solvent of 20mL deionized water and 10mL glycerol and stir evenly to obtain mixture C; add mixture B to mixture A and stir for 10min, add mixture C, stir at room temperature for 24h, centrifuge, collect solid products, wash with ethanol and deionized water to obtain chitosan coupled heterojunction; S5: The electrodeposited modified stainless steel strip was immersed in a mixed solution of dopamine-octadecylamine, heated to 37°C for reaction for 6 hours, ultrasonically washed with ethanol, dried at room temperature, immersed in a 5 mg / mL chitosan coupled heterojunction solution, kept at room temperature for 2 hours, washed with deionized water, and vacuum dried at 40°C for 8 hours to obtain an antibacterial stainless steel strip.

[0026] Comparative Example 1: A method for preparing an antibacterial stainless steel strip with high surface quality, comprising the following steps: S1: smelting a ferroalloy raw material, introducing argon into a ladle after tapping to stir the molten steel and mix it evenly, and continuously casting the molten steel into a billet; S2: subjecting the ingot to blanking, hot rolling, cold rolling, annealing, solution treatment and aging treatment in sequence to obtain a stainless steel strip substrate; S3: Using a stainless steel strip as a working electrode, a platinum plate as a counter electrode, and a saturated calomel electrode as a reference electrode, silver nanoparticles are deposited in an aqueous electrolyte through a three-electrode deposition system, taken out, and dried at 40-60°C for 4-6h to obtain an electrodeposited modified stainless steel strip; wherein, in the step S2, the specific steps of blanking include casting blanking, the blanking temperature is 1150°C; the hot rolling temperature is 1160°C; the annealing temperature is 950°C; the solid solution temperature is 1200°C, the solid solution time is 2h, the aging temperature is 620°C, and the aging time is 8h; the aqueous electrolyte is composed of 1mM silver nitrate solution, 0.5mM citric acid solution and 0.1mM potassium nitrate solution; the silver nanoparticle deposition process includes a nucleation process and a growth process, the nucleation process parameters are: the nucleation potential is -0.7V, the time is 100s, and the growth process parameters are: the growth potential is -0.1V, and the time is 3600s; S4: Add 1g chitosan to 100mL 0.8% v / v acetic acid, heat to 50°C and stir for 1-1.5h, cool to room temperature, add 1g chitosan nanoparticles, stir evenly to obtain mixture A; add 0.1g N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 0.1g N-hydroxysulfosuccinimide to ethanol and stir evenly to obtain mixture B; add 0.1g bismuth-based metal organic framework to a mixed solvent of 20mL deionized water and 10mL glycerol and stir evenly to obtain mixture C; add mixture B to mixture A and stir for 10min, add mixture C, stir at room temperature for 24h, centrifuge, collect solid products, wash with ethanol and deionized water to obtain chitosan coupled heterojunction; S5: The electrodeposited modified stainless steel strip was immersed in a mixed solution of dopamine-octadecylamine, heated to 37°C for 6 hours, ultrasonically washed with ethanol, dried at room temperature, immersed in a 4 mg / mL chitosan coupled heterojunction solution, kept at room temperature for 2 hours, washed with deionized water, and vacuum dried at 40°C for 8 hours to obtain an antibacterial stainless steel strip. Comparative Example 2: A method for preparing an antibacterial stainless steel strip with high surface quality, comprising the following steps: S1: smelting a ferroalloy raw material, introducing argon into a ladle after tapping to stir the molten steel and mix it evenly, and continuously casting the molten steel into a billet; S2: subjecting the ingot to blanking, hot rolling, cold rolling, annealing, solution treatment and aging treatment in sequence to obtain a stainless steel strip substrate; S3: Using a stainless steel strip as a working electrode, a platinum plate as a counter electrode, and a saturated calomel electrode as a reference electrode, silver nanoparticles are deposited in an aqueous electrolyte through a three-electrode deposition system, taken out, and dried at 40-60°C for 4-6h to obtain an electrodeposited modified stainless steel strip; wherein, in the step S2, the specific steps of blanking include casting blanking, the blanking temperature is 1150°C; the hot rolling temperature is 1160°C; the annealing temperature is 950°C; the solution temperature is 1200°C, the solution time is 2h, the aging temperature is 620°C, and the aging time is 8h; the aqueous electrolyte is composed of 0.5mM silver nitrate solution, 3mM citric acid solution and 0.1mM potassium nitrate solution; the silver nanoparticle deposition process includes a nucleation process and a growth process, the nucleation process parameters are: the nucleation potential is -0.7V, the time is 100s, and the growth process parameters are: the growth potential is -0.1V, and the time is 3600s; S4: Add 1g chitosan to 100mL 0.8% v / v acetic acid, heat to 50°C and stir for 1-1.5h, cool to room temperature, add 1g chitosan nanoparticles, stir evenly to obtain mixture A; add 0.1g N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 0.1g N-hydroxysulfosuccinimide to ethanol and stir evenly to obtain mixture B; add 0.1g bismuth-based metal organic framework to a mixed solvent of 20mL deionized water and 10mL glycerol and stir evenly to obtain mixture C; add mixture B to mixture A and stir for 10min, add mixture C, stir at room temperature for 24h, centrifuge, collect solid products, wash with ethanol and deionized water to obtain chitosan coupled heterojunction; S5: The electrodeposited modified stainless steel strip was immersed in a mixed solution of dopamine-octadecylamine, heated to 37°C for 6 hours, ultrasonically washed with ethanol, dried at room temperature, immersed in a 4 mg / mL chitosan coupled heterojunction solution, kept at room temperature for 2 hours, washed with deionized water, and vacuum dried at 40°C for 8 hours to obtain an antibacterial stainless steel strip. Comparative Example 3: A method for preparing an antibacterial stainless steel strip with high surface quality, comprising the following steps: S1: smelting a ferroalloy raw material, introducing argon into a ladle after tapping to stir the molten steel and mix it evenly, and continuously casting the molten steel into a billet; S2: subjecting the ingot to blanking, hot rolling, cold rolling, annealing, solution treatment and aging treatment in sequence to obtain a stainless steel strip substrate; S3: Using a stainless steel strip as a working electrode, a platinum plate as a counter electrode, and a saturated calomel electrode as a reference electrode, silver nanoparticles are deposited in an aqueous electrolyte through a three-electrode deposition system, taken out, and dried at 40-60°C for 4-6h to obtain an electrodeposited modified stainless steel strip; wherein, in the step S2, the specific steps of blanking include casting blanking, the blanking temperature is 1150°C; the hot rolling temperature is 1160°C; the annealing temperature is 950°C; the solution temperature is 1200°C, the solution time is 2h, the aging temperature is 620°C, and the aging time is 8h; the aqueous electrolyte is composed of 1mM silver nitrate solution, 3mM citric acid solution and 0.1mM potassium nitrate solution; the silver nanoparticle deposition process includes a nucleation process and a growth process, the nucleation process parameters are: the nucleation potential is -0.7V, the time is 100s, and the growth process parameters are: the growth potential is -0.1V, and the time is 3600s; S4: Add 1g chitosan and 1g chitosan nanoparticles to 100mL 0.8% v / v acetic acid, heat to 50°C and stir for 1-1.5h, cool to room temperature to obtain mixture A; add 0.1g N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 0.1g N-hydroxysulfosuccinimide to ethanol and stir evenly to obtain mixture B; add 0.1g bismuth-based metal organic framework to a mixed solvent of 20mL deionized water and 10mL glycerol and stir evenly to obtain mixture C; add mixture B to mixture A and stir for 10min, add mixture C, stir at room temperature for 24h, centrifuge, collect solid products, wash with ethanol and deionized water to obtain chitosan coupled heterojunction; S5: The electrodeposited modified stainless steel strip was immersed in a mixed solution of dopamine-octadecylamine, heated to 37°C for 6 hours, ultrasonically washed with ethanol, dried at room temperature, immersed in a 4 mg / mL chitosan coupled heterojunction solution, kept at room temperature for 2 hours, washed with deionized water, and vacuum dried at 40°C for 8 hours to obtain an antibacterial stainless steel strip. Comparative Example 4: A method for preparing an antibacterial stainless steel strip with high surface quality, comprising the following steps: S1: smelting a ferroalloy raw material, introducing argon into a ladle after tapping to stir the molten steel and mix it evenly, and continuously casting the molten steel into a billet; S2: subjecting the ingot to blanking, hot rolling, cold rolling, annealing, solution treatment and aging treatment in sequence to obtain a stainless steel strip substrate; S3: Using a stainless steel strip as a working electrode, a platinum plate as a counter electrode, and a saturated calomel electrode as a reference electrode, silver nanoparticles are deposited in an aqueous electrolyte through a three-electrode deposition system, taken out, and dried at 40-60°C for 4-6h to obtain an electrodeposited modified stainless steel strip; wherein, in the step S2, the specific steps of blanking include casting blanking, the blanking temperature is 1150°C; the hot rolling temperature is 1160°C; the annealing temperature is 950°C; the solution temperature is 1200°C, the solution time is 2h, the aging temperature is 620°C, and the aging time is 8h; the aqueous electrolyte is composed of 1mM silver nitrate solution, 3mM citric acid solution and 0.1mM potassium nitrate solution; the silver nanoparticle deposition process includes a nucleation process and a growth process, the nucleation process parameters are: the nucleation potential is -0.7V, the time is 100s, and the growth process parameters are: the growth potential is -0.1V, and the time is 3600s; S4: Add 1g chitosan to 100mL 0.8% v / v acetic acid, heat to 50°C and stir for 1-1.5h, cool to room temperature, add 3g chitosan nanoparticles, stir evenly to obtain mixture A; add 0.1g N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 0.1g N-hydroxysulfosuccinimide to ethanol and stir evenly to obtain mixture B; add 0.1g bismuth-based metal organic framework to a mixed solvent of 20mL deionized water and 10mL glycerol and stir evenly to obtain mixture C; add mixture B to mixture A and stir for 10min, add mixture C, stir at room temperature for 24h, centrifuge, collect solid products, wash with ethanol and deionized water to obtain chitosan coupled heterojunction; S5: The electro-deposited modified stainless steel strip was immersed in a mixed solution of dopamine-octadecylamine, heated to 37°C for reaction for 6 hours, ultrasonically washed with ethanol, dried at room temperature, immersed in a 4 mg / mL chitosan coupled heterojunction solution, kept at room temperature for 2 hours, washed with deionized water, and vacuum dried at 40°C for 8 hours to obtain an antibacterial stainless steel strip.

[0027] Experiment: Antibacterial experiment: All strains (Staphylococcus aureus, Escherichia coli) were activated and rejuvenated, and the rejuvenated strains were further diluted to about 10 5 Colony forming unit (CFU.mL -1 ) for antibacterial assay; 10 mm × 10 mm sample fragments were placed on agar medium and incubated at 37°C in both light and dark conditions (illuminance ≥ 20,000 Lx, using a normal LED light source) for 24 h, and the inhibition zone diameter was measured in millimeters. The experimental data are shown in Table 1 below.

[0028] Table 1 Antibacterial performance data of antibacterial stainless steel belt

[0029] Conclusion: The antibacterial stainless steel strip prepared by the present invention has excellent antibacterial properties.

[0030] The sodium citrate concentration in Comparative Example 1 was too low, and the silver nitrate concentration in Comparative Example 2 was too low; due to the lower sodium citrate and silver nitrate concentrations, Ag on the particle surface + The concentration is low, forming a so-called depletion layer, thereby inhibiting the growth of Ag nanoparticles. In the process of preparing chitosan coupled heterojunction in Comparative Example 3, chitosan and chitosan nanoparticles were added simultaneously, resulting in the destruction of the structure of some chitosan nanoparticles; in the process of preparing chitosan coupled heterojunction in Comparative Example 4, too much chitosan nanoparticles were added, resulting in an imperfect chitosan coupled heterojunction structure.

[0031] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing an antibacterial stainless steel belt with high surface quality, characterized in that: The following steps are involved: S1: smelting the ferroalloy raw materials, introducing argon into the ladle after steel is tapped, stirring the molten steel to mix evenly, and continuously casting the molten steel into billets; S2: subjecting the ingot to blanking, hot rolling, cold rolling, annealing, solution treatment and aging treatment in sequence to obtain a stainless steel strip substrate; S3: Using a stainless steel strip as a working electrode, a platinum plate as a counter electrode, and a saturated calomel electrode as a reference electrode, silver nanoparticles are deposited in an aqueous electrolyte through a three-electrode deposition system, and then taken out and dried at 40-60°C for 4-6h to obtain an electrodeposited modified stainless steel strip; S4: The electro-deposited modified stainless steel strip is immersed in a mixed solution of dopamine-octadecylamine, heated to 37-38°C for reaction for 6-7h, ultrasonically washed with ethanol, dried at room temperature, immersed in 4-5mg / mL chitosan coupled heterojunction solution, kept at room temperature for 2-3h, washed with deionized water, and vacuum dried at 40-45°C for 8-12h to obtain an antibacterial stainless steel strip.

2. The method for preparing an antibacterial stainless steel strip with high surface quality according to claim 1, characterized in that: In step S2, the specific steps of blanking include casting blanking, the blanking temperature is 1150-1160℃; the hot rolling temperature is 1160℃-1180℃; the annealing temperature is 950-960℃; the solid solution temperature is 1200-1210℃, the solid solution time is 2-2.5h, the aging temperature is 620-630℃, and the aging time is 8-8.5h.

3. The method for preparing an antibacterial stainless steel strip with high surface quality according to claim 1, characterized in that: During the preparation of the electrodeposited modified stainless steel strip, the aqueous electrolyte consists of 1 mM silver nitrate solution, 3-5 mM citric acid solution and 0.1 mM potassium nitrate solution; the silver nanoparticle deposition process includes a nucleation process and a growth process. The nucleation process parameters are: the nucleation potential is -0.7-0.8 V, the time is 100 s, and the growth process parameters are: the growth potential is -0.1 V, and the time is 600-3600 s.

4. The method for preparing an antibacterial stainless steel strip with high surface quality according to claim 1, characterized in that: In step S4, the mixed solution of dopamine-octadecylamine is composed of 2-3 mg / L dopamine hydrochloride Tris buffer solution and 50 mM octadecylamine ethanol solution.

5. The method for preparing an antibacterial stainless steel strip with high surface quality according to claim 1, characterized in that: The preparation method of the chitosan coupled heterojunction comprises the following steps: adding chitosan to 0.5-1% v / v acetic acid, heating to 50-52° C. and stirring for 1-1.5 hours, cooling to room temperature, adding chitosan nanoparticles, stirring evenly, and obtaining a mixture A; adding N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and N-hydroxysulfosuccinimide to ethanol, stirring evenly, and obtaining a mixture B; adding a bismuth-based metal organic framework to a mixed solvent of deionized water and glycerol, stirring evenly, and obtaining a mixture C; adding the mixture B to the mixture A, stirring for 10-15 minutes, adding the mixture C, stirring at room temperature for 24 hours, centrifuging, collecting the solid product, and washing with ethanol and deionized water to obtain the chitosan coupled heterojunction.

6. The method for preparing an antibacterial stainless steel strip with high surface quality according to claim 5, characterized in that: In the preparation process of chitosan coupled heterojunction, the mass ratio of chitosan: chitosan nanoparticles: N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride: N-hydroxysulfosuccinimide: bismuth-based metal organic framework is 10:10-20:1:1:

1.

7. The method for preparing an antibacterial stainless steel strip with high surface quality according to claim 5, characterized in that: The preparation method of chitosan nanoparticles comprises the following steps: adding hematoporphyrin dihydrochloride and triethylamine to dimethyl sulfoxide, stirring at room temperature in the dark for 1-1.5 hours, adding 1,3-dicyclohexylcarbodiimide and N-hydroxysuccinimide, stirring at the temperature for 12-14 hours, filtering, collecting the filtrate, adding excess anhydrous ether, separating the precipitate, washing with methanol, and obtaining hematoporphyrin ester; adding chitosan to deionized water, stirring evenly, adding a dimethyl sulfoxide solution of hematoporphyrin ester under ice bath condition, adding tetrabutylammonium bromide and 4-(N,N-dimethylamino)pyridine, stirring at room temperature in the dark for 72 hours, dialyzing with deionized water for 3 days, and freeze-drying to obtain a crude conjugate; adding the crude conjugate to a phosphate buffer, ultrasonically treating for 10-15 minutes, filtering with a 0.4-0.45 μm filter membrane, and obtaining chitosan nanoparticles.

8. The method for preparing an antibacterial stainless steel strip with high surface quality according to claim 7, characterized in that: In the preparation process of hematoporphyrin ester, the mass ratio of hematoporphyrin dihydrochloride: triethylamine: 1,3-dicyclohexylcarbodiimide: N-hydroxysuccinimide is 10:10:6.2:3.5; in the preparation process of the crude conjugate, the mass ratio of chitosan: hematoporphyrin ester: tetrabutylammonium bromide: 4-(N,N-dimethylamino)pyridine is 100:(8-12):0.5:0.

5.

9. The method for preparing an antibacterial stainless steel strip with high surface quality according to claim 5, characterized in that: The preparation method of the bismuth-based metal organic framework comprises the following steps: adding bismuth nitrate pentahydrate and trimesic acid into methanol, stirring the solution until it is clear, heating it to 120-125° C. for reaction for 24 hours, centrifuging, collecting the solid product, washing it with methanol, and vacuum drying it at 70-75° C. for 12 hours to obtain the bismuth-based metal organic framework; during the preparation process of the bismuth-based metal organic framework, the mass ratio of bismuth nitrate pentahydrate: trimesic acid is 0.84056:0.2424.

10. The antibacterial stainless steel strip prepared according to the method for preparing an antibacterial stainless steel strip with high surface quality according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of dendritic silver nanocrystalline coating using electrodeposition

    CN105386119A

  • Nano bismuth / nitrogen-doped carbon foam nanosheet two-dimensional composite material as well as preparation method and application thereof

    CN112542577A

  • Preparation method and application of bismuth-based metal organic framework material

    CN117166000A

  • Photodynamic and silver ion synergistic antibacterial hydrogel as well as preparation method and application thereof

    CN117430829A

  • Antimicrobial tailored chitosan

    US20220193244A1

Cited By

  • Stainless steel material for food-grade straw and preparation process of stainless steel material

    CN120425423A

  • A stainless steel material for food-grade straws and its preparation process

    CN120425423B